Anionic metal–organic framework as a unique turn-on fluorescent chemical sensor for ultra-sensitive detection of antibiotics. Issue 82 (16th September 2020) - Li, Chuan-Ping; Long, Wei-Wei; Lei, Zhen; Guo, Ling; Xie, Ming-Jun; Lü, Jian; Zhu, Xian-Dong
Abstract : Fabrication and engineering of an anionic metal–organic framework as a unique turn-on fluorescent chemical sensor for the ultra-sensitive detection of antibiotics. Abstract : Herein, an anionic metal–organic framework, formulated as {[Zn3 (OH)(bmipia)(H2 O)3 ]4 ·[Zn(H2 O)6.5]2 } n (FCS-3 ), was prepared from zinc ions and semi-rigid carboxylate ligands of 5-[ N, N -bis(5-methylisophthalic acid)amion] isophthalic acid (H6 bmipia) and was employed as a unique fluorescence turn-on chemical sensor for the ultra-sensitive detection of various antibiotics in the aqueous phase.